Studi Zona Gerakan Tanah dengan Metode Ahp (Analytical Hierarchy Process) Pada Daerah Curugsewu dan Sekitarnya, Kecamatan Patean, Kabupaten Kendal, Provinsi Jawa Tengah - Muhammad Andry,; Budiadi,; Rizqi Muhammad Mahbub, (ReTII, 2023)
Mass movement is a natural movement of soil mass, landslides occur in a short time and with large volumes (Djauhari Noor, 2006). Land mass transportation occurs all at once, so the level of damage caused is large. In geology, there are several factors that affect the movement of the ground, namely: slope, lithology, water, vegetation and others. This study aims to zoning the susceptibility of ground motion by using the Analytical Hierarchy Process (AHP) method. From the research conducted, the ground movement vulnerability zone in the research location is divided into 5, namely: very high vulnerability zone, high vulnerability zone, medium vulnerability zone, safe vulnerability zone and very safe vulnerability zone. The higher the vulnerability zone, the more dangerous it is to serve as a residence or plantation for the community.